2019
DOI: 10.1016/j.cherd.2019.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing droplet breakup rates of shear-thinning dispersed phase in microreactors

Abstract: A two-phase flow predictive model with the integration of conservative level-set method (LSM) and Carreau-Yasuda constitutive equation was developed herein. The LSM was chosen as a potential interface capturing scheme for elucidating the interfacial phenomena including insight into the mechanism of shear-thinning droplets. In present paper, the dynamics of shear-dependent droplet emergence, growth, detachment and translocation in a Newtonian microsystem were examined via computational fluid dynamics (CFD) anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Rostami et al [25] experimentally showed that using non-Newtonian fluids for a dispersed phase affect the system behaviour and identified flow rates for squeezing, dripping and jetting regimes for such a system. Wong et al [26,27] experimentally and numerically investigated a Carreau-Yasuda polymeric dispersed phase in a T-junction using the level set method in a range of polymer concentrations and concluded that droplet pinch-off time and the frequency are highly dependent on fluids' physical properties [26,27]. Research in this field is still lacking and more analysis for different geometries and fluids using different numerical approaches are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Rostami et al [25] experimentally showed that using non-Newtonian fluids for a dispersed phase affect the system behaviour and identified flow rates for squeezing, dripping and jetting regimes for such a system. Wong et al [26,27] experimentally and numerically investigated a Carreau-Yasuda polymeric dispersed phase in a T-junction using the level set method in a range of polymer concentrations and concluded that droplet pinch-off time and the frequency are highly dependent on fluids' physical properties [26,27]. Research in this field is still lacking and more analysis for different geometries and fluids using different numerical approaches are needed.…”
Section: Introductionmentioning
confidence: 99%
“…The interfacial force ( ) between the two fluids is governed by the following relation. is calculated from the surface area of the dispersed phase (Liu and Zhang, 2011;Jamalabadi et al, Hydrodynamics of droplet generation in microfluidic systems 2017; Wong et al, 2017Wong et al, , 2019 as follows.…”
Section: Governing Equations and Boundary Conditionsmentioning
confidence: 99%
“…However, it is found that there is no single correlation is known to predict whether there is a droplet formation or not for a specific value of c and r . Numerous computational fluid dynamics (CFD) approaches such as the volume of fluid (VOF) method, lattice Boltzmann method (LBM), phase field method (PFM), and level set method (LSM) are used in the literature to explore the hydrodynamics of droplets in emulsion/multiphase flows (Olsson and Kreiss, 2005;van der Graaf et al, 2006;De menech et al, 2008;Bashir et al, 2011;Li et al, 2012;Akhlaghi Amiri and Hamouda, 2013;Shi et al, 2014;Nekouei and Vanapalli, 2017;Yu et al, 2019;Wong et al, 2019). All the CFD approaches have primarily focused on tracking of the topological changes of the interface in motion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we solve the Carreau constitutive model [32], which includes an additional term for the viscosity at zero shear rate, and, therefore, it overcomes the limitations of the power-law viscosity model [33]. The solution of the Carreau model introduces further novelty in our works because the application of this constitutive equation in microfluidics is scarce: the current studies on the bubble hydrodynamics in Carreau fluids [34,35,36,37,38,39] limit their results to a single fluid (carboxymethylcellulose) and are valid below the tested operating conditions.⇥…”
mentioning
confidence: 99%